Increasing the Effectiveness of KPLH SAKTI (Smart, Awareness, Knowledge, Training, and Improvement) Training for the Q2 Period (April-June 2025) as an Effort to Strengthen a Resilient Safety Culture at PT Antareja Mahada Makmur Jobsite Mifa Bersaudara - Ananda Hazmidar, Tri; Wahyu Wulandari, Milla; Prayogo, Hendri; Da Maria Widodo Samosir, Tama; Triwibowo , Anton (Ridwan Institute, 2025)
The internal training program of KPLH (SAKTI) at PT Antareja Mahada Makmur Jobsite Mifa has not been effective in forming safe behavior. The main problems include low training implementation (30.8% of the plan), low employee participation (6.2% of 2,830 people), and the dominance of unsafe behavior and personal factors as causes of work accidents. Based on the results of the analysis of the identification of the root causes of the ineffectiveness of the internal training of KPLH SAKTI is due to the absence of a real-time monitoring system, suboptimal trainer appointment, the absence of TNA-based needs analysis, and the absence of a post-training evaluation mechanism. The innovation of the Mining Occupational Safety and Health (KPLH) Training system (SAKTI) which is more structured and digitally based has resulted in a significant increase in participant participation (Q1: 6.2% to 15.3% in Q2), increased training implementation (Q1: 30.8% to 53.8% in Q2), as well as evaluation of learning outcomes with the achievement of a score of >70 and the implementation of safe behavior in the workplace. to 15.3%, training implementation realization at 53.8%, and learning outcome evaluations above 70, which contribute to the implementation of safe behavior in the field. Other impacts achieved from this innovation include strengthening a behavior-based safety culture, improving the quality of the training system in accordance with the standards of the Director General of Mineral and Coal Mining Decree No. 185/2019, and contributing to the development of human resource competencies in K3.